2012
DOI: 10.3899/jrheum.111433
|View full text |Cite
|
Sign up to set email alerts
|

Autofeedback from Ultrasound Images Provides Rapid Improvement in Palpation Skills for Identifying Joint Swelling in Rheumatoid Arthritis

Abstract: Our results suggest that autofeedback from US assessment provides quick improvement in palpation skills for identifying joint swelling in patients with RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…We have previously reported that clinical examination skills improve through feedback learning by comparing the results of conventional clinical joint examination with those of articular US 4) . To improve the clinical examination skills and treatment quality, it is important to identify highly valid and effective methods in order to use articular US as a learning and treatment tool.…”
Section: Assessment With Palpation and Self-learningmentioning
confidence: 99%
“…We have previously reported that clinical examination skills improve through feedback learning by comparing the results of conventional clinical joint examination with those of articular US 4) . To improve the clinical examination skills and treatment quality, it is important to identify highly valid and effective methods in order to use articular US as a learning and treatment tool.…”
Section: Assessment With Palpation and Self-learningmentioning
confidence: 99%
“…Cases in which US detected a PD signal progresses at high probability to persistent arthritis requiring antirheumatic agents such as methotrexate 4) . It led to the improvement of palpation techniques with which physicians can independently confirm the correctness of their examination findings through anatomical understanding of the lesion using US 13) . Moreover, in our experience, the patient developed an understanding of the pathological conditions through US images, facilitating understanding of the necessary changes in the treatment strategy.…”
Section: Usefulness Of Us In Early and Differential Diagnosesmentioning
confidence: 99%
“…A number of studies have shown that ultrasound detects synovial inflammation more sensitively than does clinical joint examination [2][3][4][5] and ultrasound-detected synovitis correlates well with magnetic resonance imaging (MRI) [4,[6][7][8] and histopathological findings [9,10]. As synovial inflammation is the most characteristic pathophysiology of rheumatoid arthritis (RA), sonographic assessment of synovial inflammation has been shown to improve the accuracy of diagnosis [11][12][13][14][15][16], optimize the assessment of disease activity [15,[17][18][19][20][21][22], predict relapse after discontinuation of biological treatment [23], and also improve the physicians' joint examination skill [24] in the management of RA. Therefore, a rapidly increasing number of rheumatologists now use ultrasound for the assessment of synovial inflammation in daily practice, training, and education [25].…”
Section: Introductionmentioning
confidence: 99%